2009
DOI: 10.1590/s0100-69912009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento cirúrgico do megaesôfago no Hospital de Clínicas da UNICAMP - fatores associados a melhores ou a piores resultados

Abstract: ABSTRACT ABSTRACT ABSTRACTObjectives: Objectives: Objectives: Objectives: Objectives: To verify some possible factors, which would be associated with better or worse results for surgical treatment of megaesophagus. Methods Methods Methods Methods Methods: There were 417 patients operated on for megaesophagus, but only 390 medical charts were analyzed between 1989 and 2005. The presence of intraoperative and postoperative complications and the maintenance of severe dysphagia complaints were evaluated in a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…According to Oliveira et al [54], there are an estimated 300,000 individuals with megacolon, the main symptoms of which are constipation and fecal impaction. Silva et al [55], reported alterations in intestinal secretion, absorption and motility in these patients, which culminate in mega-syndromes (dilated area upstream from the achalasic segment).…”
Section: Reviewmentioning
confidence: 99%
“…According to Oliveira et al [54], there are an estimated 300,000 individuals with megacolon, the main symptoms of which are constipation and fecal impaction. Silva et al [55], reported alterations in intestinal secretion, absorption and motility in these patients, which culminate in mega-syndromes (dilated area upstream from the achalasic segment).…”
Section: Reviewmentioning
confidence: 99%
“…There is no definite treatment for CME since the functional changes are permanent and progressive. Treatment includes a clinical approach, with a change in Physiotherapy in the surgical treatment of Chagasic Megaesophagus Vento DA, et al eating habits and medication, and, in more advanced cases or cases presenting greater clinical repercussions, surgery [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Dysphagia is the manifestation that leads the patient to seek medical advice, and is generally progressive 12 , 14 . Megaesophagus is classified according to the transverse diameter of its body, ranging from 1 to 4 (Mascarenhas' score).…”
Section: Introductionmentioning
confidence: 99%
“…Megaesophagus is classified according to the transverse diameter of its body, ranging from 1 to 4 (Mascarenhas' score). The treatment is surgical and this classification assists the choice of surgery 8 , 12 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation